Trimethylamine N-oxide (TMAO) as a New Potential Therapeutic Target for Insulin Resistance and Cancer - Oellgaard, Jens; Abitz Winther, Signe; Schmidt Hansen, Tobias; Rossing, Peter; Johan von Scholten, Bernt (Current Pharmaceutical Design, 2017)
Background: The intake of animal products in food has been associated with both the development of insulin resistance and gastrointestinal cancers (GIC). Through the digestion of animal protein and other constituents of animal products, the commensal bacteria in the gut (the gut microbiota) forms metabolites that can contribute to the development of both insulin resistance and cancer. Trimethylamine-N-Oxide (TMAO) is such a molecule and has recently drawn a lot of attention as it may be a risk factor for - and a link between - the gut microbiota and cardiovascular and renal disease. Further, TMAO is anticipated to have significance as a biomarker of - or even an independent risk factor for - other undesirable conditions, including insulin resistance and GIC. TMAO originates from a precursor, trimethylamine (TMA) that is a metabolite of various precursors; mainly choline and carnitine from ingested foods. Methods: We review the literature on TMAO as a shared risk factor and/or pathway between insulin resistance and GIC risk and take the reader through the literature of interventions that could reduce formation of TMAO and thereby the risk of insulin resistance and GIC. The purpose of the work is to generate a hypothesis to be tested in preclinical and clinical studies. Results: TMAO seems to be associated with both insulin resistance and GIC risk and also with atherosclerotic cardiovascular disease. One shared pathway is the formation of N-Nitroso compounds, a group of metabolites that can cause DNA-damage and epigenetic changes. Levels of TMAO can be reduced by limiting the dietary intake of certain foods, most importantly animal products. Further, certain drugs, namely Meldonium and 3,3-dimethyl- 1-butanol, may inhibit the formation of TMAO by inhibiting bacterial enzymes. Conclusions: The TMAO pathway and its metabolites are possibly involved in the development of two major health problems: insulin resistance and cancer. Within these pathways novel therapeutic targets may be identified. Further research is needed in order to verify existing or develop new pharmacological agents that modify these pathways and reduce the risk of insulin resistance and GIC.
Keywords: microbiome